PERAN SERTA MASYARAKAT DALAM PELAKSANAAN AMDAL DI ERA OTONOMI DAERAH - Ardhana, IPG. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 2)
This Article is written with a view to know role and socialization of the autonomous municipality.This Article represent the normative legal research that is concern with legislation approach (the statute approach), case study approach (the case approach), approach by factual (the fact approach) and the approach of analisial legal concept (analytical conceptual approach) and also the bibliography approach (the library approach) that is the collection of the reading materials relaited with this topic of problems..From result of this article we can know that the role and the socialization in the automous municipality still have an illusional character and cannot fulfill clearly and accurately it’s function. Because in the arena of politics the determination process of bribes and corruptiones, so minutes which is agreed at early in the meeting or conclusiones wich is written in the minute of meeting often different from the determined public policies. To diminish these problems we extremely need the essential quarantee that socializational requiamentes or aspirationes which are integrated in the public policies must be based on partisipative statutes concerning with the autonomous municipality.
Keywords: Role and also the society, Autonomous municipality, Essential quarantee